Pharmacotherapeutic medications and oral care products in the appointment of a dentist - Mazur, I.; Suprunovych, I. (Actual Dentistry, 2018)
Summary. This article presents a comparative analysis of prescriptions of pharmacotherapeutic drugs, which are most often prescribed by Ukrainian dentists in their practical activities. Surveys of dentists were conducted under the aegis of the non-governmental organization «Ukrainian Dental Association», companies Morion, MedExpert, ProximaResearch and Shupyk National Medical Academy of Postgraduate Education during dental conferences during 2016–2017. Monitoring of prescriptions of medicinal preparations for various pharmaceutical groups was conducted. The analysis of the most widely used pharmacotherapeutic drugs by dentists for two years is presented. Key words: medications, comparative analysis, questionnaire.